Revisiting nitrates use in pre-shock state of contemporary cardiogenic shock classification - Kaddoura, Rasha; Patel, Ashfaq; Arabi, Abdul Rahman (Frontiers in Cardiovascular Medicine, 2024)
Patients at each shock stage may behave and present differently with a spectrum of shock severity and adverse outcomes. Shock severity, shock aetiology, and several factors should be integrated in management decision-making. Although the contemporary shock stages classification provided a standardized shock severity assessment, individual agents or management strategy has not yet been studied in the context of each shock stage. The pre-shock state may comprise a wide range of presentations. Nitrate therapy has potential benefit in myocardial infarction and acute heart failure. Herein, this review aims to discuss the potential use of nitrate therapy in the context of the pre-shock state or stage B of the contemporary shock classification given its various presentations.